(untitled) (Jurnal Manajemen Bisnis, 2026)
This study explores the effectiveness of the Smart Card application as a digital innovation in the payment and student monitoring system at the Darul Hikmah Islamic Boarding School in Pekanbaru, with an in-depth analysis through the lens of Ibn Asyur’s maqashid sharia. The main objective is to assess the application’s contribution to financial transparency, student behavior monitoring, and its compliance with sharia principles in the context of modern Islamic education. Using qualitative methods based on in-depth interviews with stakeholders such as the principal, teachers, students, parents, and administrative staff, as well as analysis of related literature, this study reveals that the Smart Card successfully increases the efficiency of non-cash transactions, minimizes the risk of data loss, and enables real-time monitoring that supports student discipline. However, challenges such as high administrative costs and technical limitations (e.g., long queues and network) still hamper optimization. From the perspective of Ibn Asyur’s maqasid sharia, this application embodies maqasid al-’ammah (public welfare through justice and trustworthiness), maslahah daruriyyah (protection of wealth), hajiyyah (ease of life), and tahsiniyyah (formation of noble morals), while also supporting maqasid al-khasah in educational transactions. In conclusion, Smart Card is an effective tool for the integration of technology and sharia, although improvements are needed to fully achieve maximum benefits in Islamic boarding school education.